2018
DOI: 10.31638/ijprs.v7.i3.00047
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Enhancement of Clarithromycin Using Ternary Cyclodextrin Complexation

Abstract: The research work presented is new and never been done earlier. Clarithromycin, a semi-synthetic macrolide antibiotic derived from erythromycin having low solubility and high permeability falling in class-II of Biopharmaceutical Classification System (BCS). The drug is practically insoluble in water exhibiting dissolution rate limited absorption. The objective of the research work increasing in the solubility, release properties of Clarithromycin and improve the bioavailability of Clarithromycin using ternary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The efficacy of the β-CD/clarithromycin complex against Mycobacterium avium in human peripheral blood monocyte-derived macrophages was slightly lower than that of the free drug, possibly due to the high stability of the IC. In a different approach, the solid-state ternary complexes of clarithromycin with β-CD and citric acid (1:1:1) were prepared by co-evaporation and lyophilisation [ 218 , 219 ] or with polymer Soluplus [ 220 ]. The obtained results suggested that the lyophilisation method afforded a higher degree of amorphous unit than co-evaporation, and a part of the guest molecule was located in the β-CD cavity.…”
Section: Macrolidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of the β-CD/clarithromycin complex against Mycobacterium avium in human peripheral blood monocyte-derived macrophages was slightly lower than that of the free drug, possibly due to the high stability of the IC. In a different approach, the solid-state ternary complexes of clarithromycin with β-CD and citric acid (1:1:1) were prepared by co-evaporation and lyophilisation [ 218 , 219 ] or with polymer Soluplus [ 220 ]. The obtained results suggested that the lyophilisation method afforded a higher degree of amorphous unit than co-evaporation, and a part of the guest molecule was located in the β-CD cavity.…”
Section: Macrolidesmentioning
confidence: 99%
“…The dissolution rate at pH 5.0 was similar for pure clarithromycin and its ternary complexes, whereas at pH 6.8 the clarithromycin release was much faster from the complex (about 80% after 40 min) than from the pure drug (about 40% at the same time) [ 219 ]. Formulations with a Soluplus concentration of 20% w / w of the drug content and 30% ethanol as a solvent showed more than 80% of drug release at the end of one hour [ 220 ].…”
Section: Macrolidesmentioning
confidence: 99%